Mapping arealisation of the visual cortex of non-primate species: lessons for development and evolution - Homman-Ludiye, Jihane; Bourne, James A. (Frontiers in Neural Circuits, 2014)
In order to integrate and interpret visual stimuli and build a representation of the surrounding environment, the visual cortex is organised in anatomically distinct and functionally unique areas. Each area processes a particular aspect of the visual scene, with the signal flowing from one area to the next in a bottom-up processing sequence. Areal borders can be demarcated both functionally by systematic electrophysiology mapping, and anatomically by sharp changes in cellular distribution and molecular expression profiles. Primates, including humans, are heavily dependent on vision, with approximately 50% of their neocortical surface dedicated to visual processing and possess many more visual areas than any other mammal, making them often the model of choice to study visual arealisation. However, the recent identification of differential gene expression profiles between cortices in a number of species has allowed for the introduction of non-primate animal models in the field to better understand development and evolution. Profiling the mosaic of visual areas in less complex species was pivotal in understanding the mechanisms responsible for patterning the developing neocortex, specifying area identity as well as the evolutionary events that have allowed for primates to develop more areas. In addition, species with fewer areas provide a simpler system in which to study and map cortical connectivity. In this review we focus on non-primate species that have contributed to elucidating the evolution and development of the visual cortex, including small nocturnal species and carnivores. We present the current understanding of the mechanisms supporting the establishment of areal borders during development and the limitations of the predominant mouse model and the need for alternate species.